Why has the literature on corporate governance and firm performance yielded mixed results? (2014)
This paper reviews the empirical literature on corporate governance and firm performance and finds that it has yielded mixed results. The paper argues that a primary reason for this situation is that the relevant theories have not been applied to the class of phenomena they were designed to explain. In particular, the literature that focuses on ownership structure and firm performance employs entrepreneurial agency theories of the firm but applies them to managerial firms where ownership is separated from control. This is evidenced by the fact that firms in which managerial ownership is close to zero percent are included in the samples. Conversely, empirical work centered on the relationship between board composition and firm performance (which relies on managerial agency theories of the firm) not only does not make sure that the firms in their samples are characterized by the separation of ownership and control, but it also ignores the alternative managerial agency theory concerning the agency costs of free cash flows. Additionally, the paper maintains that other approaches, such as that which studies the relationship between indices of anti-takeover provisions and firm performance, do not rely on any particular theory and for this reason are beset by problems of interpretation. The paper concludes with recommendations for avoiding the drawbacks and achieving future progress.